2022
DOI: 10.3389/fmicb.2022.761873
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Comparison Between Shotgun Metagenomics and Sanger Sequencing of the 16S rRNA Gene for the Etiological Diagnosis of Infections

Abstract: Bacteriological diagnosis is traditionally based on culture. However, this method may be limited by the difficulty of cultivating certain species or by prior exposure to antibiotics, which justifies the resort to molecular methods, such as Sanger sequencing of the 16S rRNA gene (Sanger 16S). Recently, shotgun metagenomics (SMg) has emerged as a powerful tool to identify a wide range of pathogenic microorganisms in numerous clinical contexts. In this study, we compared the performance of SMg to Sanger 16S for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…The use of an Excel randomization function in the present study was intended to reduce any bias while assigning individual samples to the various pools within each group. A limitation of the 16S rRNA sequencing approach used in the present study is its inability to detect less abundant taxa in comparison to the relatively advanced and more sensitive metagenomic next generation sequencing (NGS) approach (Durazzi et al., 2021 ; Lamoureux et al., 2022 ). Future studies involving metagenomic NGS of individual samples are required to further our understanding of the uterine microbiome in healthy mares and mares with endometritis.…”
Section: Discussionmentioning
confidence: 97%
“…The use of an Excel randomization function in the present study was intended to reduce any bias while assigning individual samples to the various pools within each group. A limitation of the 16S rRNA sequencing approach used in the present study is its inability to detect less abundant taxa in comparison to the relatively advanced and more sensitive metagenomic next generation sequencing (NGS) approach (Durazzi et al., 2021 ; Lamoureux et al., 2022 ). Future studies involving metagenomic NGS of individual samples are required to further our understanding of the uterine microbiome in healthy mares and mares with endometritis.…”
Section: Discussionmentioning
confidence: 97%
“…Hong et al investigated the diagnostic accuracy of sMGS vs tMGS in sonicate fluid and found similar positive percent agreements: 72% for tMGS and 73% ( P = .83) for sMGS. Interestingly, another study found no significant difference between 16S rRNA PCR followed by Sanger sequencing and sMGS evaluated on 67 diverse tissue and fluid samples (including heart valves) [ 24 ]. However, all clinical metagenomics methods should be compared with caution.…”
Section: Discussionmentioning
confidence: 99%
“…However, in primary non-sterile body sites, this may introduce a critical diagnostic bias. The performance in bacterial detection and identification was compared between shotgun metagenomics and 16S amplicon-based sequencing, where shotgun metagenomics showed a slightly higher sensitivity (46.3% vs. 38.8%) than 16S [ 119 ]. Similarly, Gu et al compared shotgun metagenomic sequencing using Illumina (short-read) and Nanopore sequencing (long-read) platforms for pathogen identification and validated the results with traditional culture-based methods and also with 16S and 28S-ITS PCRs for bacterial and fungal species.…”
Section: Focus On Bacterial Communitiesmentioning
confidence: 99%